Linear Neutral Receptors for Anions: Synthesis, Structure and Applications - Cholewiak, Agnieszka; Stepniak, Pawel; Jurczak, Janusz (Synthesis, 2018)
A selective digest of linear anion receptors based on different aromatic skeletons is presented. Since the structures of anions vary from one to another, different strategies have been developed over recent years in order to bind anions efficiently and selectively. Rigidity, number of hydrogen bond donors, steric hindrance, and special preorganization of linear receptors are analyzed to shed light on the rational design of anion receptors.1 Introduction2 1,3- and 1,2-Benzene Derivatives3 1,3- and 5,7-Azulene Derivatives4 1,8-Naphthalene Derivatives5 1,8-Anthracene Derivatives6 2,6-Pyridine Derivatives7 2,5-Pyrrole Derivatives8 Diamidoarenodipyrrole Derivatives9 Carbazole Derivatives10 DITIPIRAM Derivatives11 Conclusion
Keywords: supramolecular chemistry; anion recognition; neutral receptors; platforms